(untitled) (Bioagro, 2020)
Molecular markers are useful tools for evaluating genetic diversity and determining cultivar identity. Thirty simple-sequence-repeat (SSR) markers were selected in order to evaluate the genetic diversity within 76 cultivars of the Ecuadorian Rice Program for breeding. One-hundred-ninety-four alleles were detected in 22 SSR polymorphic markers, number of alleles per marker ranging from 2 to 24, with an average of 9 alleles per locus. The sizes of the alleles varied between 62 to 280 bp, with an average polymorphism information content value of 0.624, ranging from 0.202 (RM125) to 0.943 (RM413), indicating significant genetic diversity among and within the rice accessions. The average observed heterozygosity (Ho) was 0.086, while average expected genetic diversity (He) was 0.667. A set of eight of the polymorphic SSR markers produced seventeen unique alleles for the genotypes studied and could distinguish released cultivars from the rest of accessions. A dendrogram constructed using the unweighted pair-group method with arithmetic means (UPGMA) grouped the 76 rice materials in four well differentiated major clusters whereas the Structure program without any a priori information provided support for the existence of three genetically distinct clusters (K = 3).